2022
DOI: 10.36103/ijas.v53i5.1618
|View full text |Cite
|
Sign up to set email alerts
|

Response Postharvest Quality of Pomegranates to Thermal Treatments, Immersing in Black Seed and Flaxseed Oils

Abstract: This study was carried out to investigate  thermal treatments, immersing in black seed and flaxseed oils on postharvest quality pomegranate fruits cv. Salakhan . Fruits were randomly divided into two experiments: First, thermal treatment by which fruits are immersed for four minutes at 25, 40 and 50°C in hot water (HW), and fruits are exposed to hot air (HA) for one hour at 40 and 50°C plus control treatment. Second, fruits are immersed for 4 minutes in 1 and 2% for the black seed and flaxseed oil, plus contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…Therefore, flaxseed oil may possess some advantages to be applied as an additional ingredient in the coating of foods and fruits. Recent studies have shown that the use of flaxseed oil has a big role in an extended storage period of pomegranate fruits which causes reduced weight loss and cold damage and prolongs the storage period (3). Several studies have indicated that the use of black seed oil to the extent the storage period of pomegranate fruits caused reduced weight loss and cold damage and prolonged storage period, as well as reduced the percentage of microbial damage and maintaining the quality and marketability of pomegranate fruit (3,21), and in banana fruits (24).…”
Section: ‫العراقية‬ ‫الزراعية‬ ‫العلوم‬ ‫مجلة‬mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, flaxseed oil may possess some advantages to be applied as an additional ingredient in the coating of foods and fruits. Recent studies have shown that the use of flaxseed oil has a big role in an extended storage period of pomegranate fruits which causes reduced weight loss and cold damage and prolongs the storage period (3). Several studies have indicated that the use of black seed oil to the extent the storage period of pomegranate fruits caused reduced weight loss and cold damage and prolonged storage period, as well as reduced the percentage of microbial damage and maintaining the quality and marketability of pomegranate fruit (3,21), and in banana fruits (24).…”
Section: ‫العراقية‬ ‫الزراعية‬ ‫العلوم‬ ‫مجلة‬mentioning
confidence: 99%
“…Recent studies have shown that the use of flaxseed oil has a big role in an extended storage period of pomegranate fruits which causes reduced weight loss and cold damage and prolongs the storage period (3). Several studies have indicated that the use of black seed oil to the extent the storage period of pomegranate fruits caused reduced weight loss and cold damage and prolonged storage period, as well as reduced the percentage of microbial damage and maintaining the quality and marketability of pomegranate fruit (3,21), and in banana fruits (24). Chitosan is a positively charged, high molecular weight polysaccharide that is soluble in dilute organic acids and can extend shelf life by controlling spoilage of many fruits such as pears, longan, and strawberries (19,18).…”
Section: ‫العراقية‬ ‫الزراعية‬ ‫العلوم‬ ‫مجلة‬mentioning
confidence: 99%